Indication of laboratory parameters for kidney diseases at King Fahad Medical City, Riyadh, Saudi Arabia (American Journal of Medical Science and Innovation, 2025)
End-stage renal disease (ESRD), chronic kidney disease (CKD), and acute kidney failure (AKF) are serious global health issues that contribute to high sickness and death rates. This King Fahad Medical City study investigated the importance of reliable biomarker monitoring and early treatment to enhance patient outcomes. 220 people had their serum levels of albumin, C-reactive protein (CRP), urea, creatinine, salt and phosphate assessed. Creatinine (χ² = 60.73, p < 0.001), urea (χ² = 48.66, p < 0.001), phosphate (χ² = 19.20, p = 0.004), sodium (χ² = 14.10, p = 0.029) and body weight (χ² = 13.24, p = 0.039) showed significant differences across diagnostic groups, according to the Kruskal-Wallis test. Significant activity was indicated by the highest CRP values (103.9 mg/L; 95% CI: 83.9–123.9 mg/L) in AKF patients, whereas the highest average creatinine levels (428.6 µmol/L; 95% CI: 330.0–527.2 µmol/L) were seen in ESRD patients. The above results show that every disease has an unique biomarker signature. Also a gender study revealed that, on average, male patients weighed 7.29 kg heavier than female patients (t = 2.739, p = 0.007). The study shows that kidney-related illnesses may be effectively treated with biomarker-based diagnostics.Important biomarkers for CKD, ESRD and AKF detection include creatinine, urea, CRP and sodium. This highlights how helpful these indicators are for supporting timely diagnosis, improving clinical intervention techniques and directing customized treatment plans.